Classes de Stiefel-Whitney e de Euler - Barbosa, Alex Melges [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Neste trabalho, apresentaremos uma descrição axiomática das classes de Stiefel-Whitney e, assumindo válidos estes axiomas, mostraremos algumas de suas aplicações. Posteriormente, definiremos as classes de Stiefel-Whitney e mostraremos que esta definição satisfaz os axiomas, além de garantir a unicidade das classes de Stiefel-Whitney. Por fim, definiremos a classe de Euler e mostraremos algumas de suas aplicações, bem como sua relação com as classes de Stiefel-Whitney.

In this work, we will present an axiomatic description of the Stiefel-Whitney classes and, taking these axioms true, we will show some of their applications. After that, we will define the Stiefel-Whitney classes and we will show this definition meets the axioms, besides it ensures the unity of the Stiefel-Whitney classes. Lastly, we will define the Euler class and we will show some of its applications as well as its relationship with the Stiefel-Whitney classes.
Stiefel-Whitney and Euler Classes
Keywords: Variedades C∞; Fibrados vetoriais; Classes de Stiefel-Whitney; Fibrados orientados; Classe de Euler; C∞ Manifolds; Vector bundles; Stiefel-Whitney Classes; Oriented bundles; Euler Class